Above the books of the Banga brothers and Eliška Tanzer: Stepping into the literary mainstream? - Viková, Lada (Romano džaniben, 2023)
The review article is devoted to the content analysis of three autobiographical books written by young Roma authors, published between 2021 to 2022. The moments that these authors emphasize in their books complement each other and help create a narrative about stress and danger, which the generation of today's Roma in their thirties and forties faced in their childhood and adolescence, and which shaped it to a certain extent. All three authors are united by the need to cope with the traumas of their youth and the desire to achieve a better position than "society" or circumstances predetermined for them at the beginning of their careers. This text seeks, among other things, an answer to the questions to what extent these three authors approach their autobiographical writing from a critical sociological point of view and whether they manage to name and describe the mechanisms of society that pushed and keep the Roma on the margins of society. At the same time, it touches on the question of whether these three books can be perceived as a step of Roma writing towards mainstream literature.